Asia Pacific Breweries Foundation Signature Art Prize 2008. - Toh, Joyce (Singapore : Singapore Art Museum Singapore, 2008)
Remissa, Mak ; Meas Sokhorn ; Svay Ken ; Gao Shiqiang ; Zheng Bo ; Zheng Duanxiang ; Iranna, G.R. ; Kongphat Luangrath ; May Chandavong ; Fuad Osman, Ahmad ; Azizan Rahman Paiman, Noor ; Yee I-Lann ; Doriderem, Davaa ; Erdenebayar, Monkhor ; Enkhjim, Tsultem ; Cheesman, Iain ; Bush, Kushana ; Trusttum, Philip ; Waswas, Daniel ; Morububuna, Martin ; Deko, Tom ; Prvacki, Milenko ; Chandrasekaran, S. ; Yeo Chee Kiong ; Krishantha Baragama Arachchi, Anura ; Kumara Kalubadana, Sanath ; Pothupitye Acharige, Somapala ; Phunsombatlert, Bundith ; Chimnok, Chakkrit ; Sanpitak, Pinaree ; Hoang Duong Cam ; Nguyen Quang Huy ; Vuong Van Thao
biog., ind. tent., gr. tent., prijzen p. 70-97
Engels
Exhibition. Asia Pacific Breweries Foundation Signature Art Prize 2008. Singapore. Art Museum Singapore. Singapore Art Museum Singapore, 10.10.2008 - 16.11.2008.
boek